2017
DOI: 10.4028/www.scientific.net/ssp.268.198
|View full text |Cite
|
Sign up to set email alerts
|

DC and Thermal Conductivity of Lithium Zinc Phosphate Glasses

Abstract: The phosphate glasses, with composition (60-x)P2O5-25ZnO-(15+x)Li2O where 0.0 ≤ x ≤ 5.0 mol% are prepared by conventional melt quenching method. The amorphous nature of the glass is determined by X-Ray Diffraction (XRD). The physical properties are measured in term of their density and molar volume. Glass density is found to increase from 2.700 to 2.785 g cm-3 whereas molar volume is found to decrease from 40.735 to 37.488 cm3 mol-1 with respect to Li2O content. The DC measurements are done by using four point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…AC conductivity spectra [12,13,15,27] have been studied and analyzed at numerous temperatures using equation (2) and such spectra at a particular temperature for glass-nanocomposites and their crystalline counterparts have been presented in figure 7. For comparison, complex impedance plots for x=0.1 and its crystalline counterpart are included in the inset of figure 7.…”
Section: Ac Conductivity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…AC conductivity spectra [12,13,15,27] have been studied and analyzed at numerous temperatures using equation (2) and such spectra at a particular temperature for glass-nanocomposites and their crystalline counterparts have been presented in figure 7. For comparison, complex impedance plots for x=0.1 and its crystalline counterpart are included in the inset of figure 7.…”
Section: Ac Conductivity Studymentioning
confidence: 99%
“…Initiatives [12] have been taken to enhance conductivity in lithium-ion conducting glassy systems using the mechanism of dissolving alkali oxides such as Li 2 O, LiCl and Na 2 O into other oxide glassy matrices, which may be caused due to mixed former effects. Recent developments [13] on electrical and thermal conductivity of P 2 O 5 -ZnO-Li 2 O glassy systems have clearly exhibited how the incorporation of Li 2 O acts as a major part of the process of modification of the network structure. It is also observed that high amounts of Li + and their small inter-particle contacts are responsible for thermal conductivity up to an extent in this glassy system due to high lattice waves.…”
Section: Introductionmentioning
confidence: 99%